Managing Conflicts with Wildlife: Living with Bears - William M. Giulliano; Holly K. Ober; Lauren Watine; Eric Hellgren; Raoul Boughton; Dave Telesco (EDIS)
Black bears are omnivorous, enigmatic animals that help maintain healthy forests by dispersing seeds of plants they eat. Bear watching is a favorite pastime for many Floridians throughout the state. Bears are generally secretive and rarely a problem for people. But there are rare situations where they can become dangerous or damaging. In this 4-page fact sheet, we present some facts about bears, describe dangers and problems they may cause, and provide suggestions on how to cope with these issues. Written by William M. Giuliano, Holly K. Ober, Lauren Watine, Eric Hellgren, Raoul Boughton, and Dave Telesco, and published by the UF Department of Wildlife Ecology and Conservation, December 2014.